Integrated Wavefront Sensing and Processing Method Utilizing Optical Neural Network - Gang Luo; Yuanchao Geng; Deen Wang; Qiang Yuan; Dongxia Hu; Wanguo Zheng (Photonics, 2024)
Wavefront sensors and processors are vital components of adaptive optical (AO) systems, directly impacting the operating bandwidth. As application scenarios become increasingly complex, AO systems are confronted with more extreme atmospheric turbulence. Additionally, as optical systems scale up, the data processing demands of AO systems increase exponentially. These challenges necessitate advancements in wavefront sensing and processing capabilities. To address this, this paper proposes an integrated wavefront sensing and processing method based on the optical neural network architecture, capable of directly providing control coefficients for the wavefront corrector. Through simulation and experimentation, this method demonstrates high sensing precision and processing speed, promising to realize large-scale, high-bandwidth AO systems.